Implicit Bilingualism in the Prose of Fazil Iskander - Marina. V. Bitokova; Arina S. Kankulova (Polylinguality and Transcultural Practices, 2024)
The study examines the peculiarities of the manifestation of Fazil Iskander’s bilingualism in the works “Sandro of Chegem”, “Childhood of Chik” and “Sofichka”. They were chosen as the main research material because they represent the most complete “Abkhazian” metatext of the writer: the action takes place in Abkhazia, the subject of the image is often not only folk types of character, but also the traditional way of life, folk customs and rituals. Such immersion in the cultural context cannot do without language switching, which provides the effect of authenticity. The relevance of such research is dictated not only by the relentless interest of modern humanities in the phenomenon of poly- and bilingualism, but also by the need to attribute the work of the Russian writer of Iranian-Abkhaz origin: simultaneously with the popularity of his works and the reader’s interest in them, there is a shortage of scientific understanding of Iskander’s creative heritage. The purpose of our research is the peculiarities of the mechanisms of bilingualism in the work of Fazil Iskander. His bilingualism, due to the fact of his birth in the national republic and upbringing in a Russian-speaking environment, was reflected in the linguistic features of the works he created. These features include calcified speech formulas and etiquette phrases, the specifics of nominology (in particular, the nicknames that the writer uses), the traditions of Abkhazian oral eloquence. All these ways help Iskander to fill the novel and the cycles of stories with a poetic attitude to the depicted idyll of folk life, on the other hand, solves a lot of pragmatic writing tasks. The result of this article can be considered the definition of the peculiarities of Fazil Iskander’s bilingualism, which manifests itself at various levels - phonetic, word-formation, syntactic, as well as in orientation to the traditions of the Abkhaz oral narrative, the features of traditional eloquence.